Kearifan Lokal: Tradisi Ambengan dalam Perspektif Mistisme Islam (Studi Kasus Desa Sengon Sar Kec. Aek Kuasan Kab. Asahan) - Winarva, Al Imran; Abbas, Mardhiah; Faza, Abrar M. Daud (YASIN, 2024)
Local wisdom is defined as ideas, opinions, convictions, and moral behavior that upholds wisdom ideals in a community. The Ambengan tradition is one example of local wisdom a noble community value that is practiced and passed down from generation to generation. Among the customs of rural communities that are still practiced and maintained is the Ambengan tradition. Based on the nature of the problem, qualitative research is the type that is employed; it is descriptive research that employs qualitative methods. Primary materials included documentation of events, in-depth interviews with the Ambengan tradition, and observation made by going to the tradition's location. This research concludes that the Ambengan tradition is a tradition based on the studies that have been conducted executed by the people of Sengon Sari Village and is motivated by their appreciation to Allah SWT for all of His favors. Putting this tradition into practice also gives the Ambengan people a platform for their artistic and creative expression. The Ambengan tradition's philosophical significance for society is that it upholds religious principles, which include appreciation, almsgiving, friendship, and worship.